Intrinsic stresses in DLC coatings deposited in modes of DC and pulse bias potentials - Kalinichenko, A.I.; Perepelkin, S.S.; Strel’nitskij, V.E. (Вопросы атомной науки и техники, 2015)
Formula for intrinsic stress calculation in coatings deposited from ion flux in the pulse potential mode is derived. The criterion of applicability of derived formula is proposed which permits determining critical parameters of the pulse potential mode. Calculation of stress in DLC coatings at deposition of low-energy ions C+ from filtered vacuum arc plasma is presented. The qualitative agreement of calculated stresses with experimental data is stated. The important role of deposition temperature for intrinsic stress control in deposited coating is noted. Дан вывод формулы для расчета внутренних напряжений в покрытиях, осаждаемых из потока ионов в режиме импульсного потенциала. Предложен критерий применимости полученной формулы, позволяющий определить критические параметры режима импульсного потенциала. Приведены расчеты напряжений в алмазоподобных покрытиях при осаждении низкоэнергетических ионов C+ из фильтрованной плазмы вакуумной дуги. Констатируется качественное согласие расчетных напряжений с экспериментальными данными. Отмечается важная роль температуры осаждения при контроле внутренних напряжений в осаждаемом покрытии. Наведено виведення формули для розрахунку внутрішньої напруги в покриттях, що осаджуються з потоку іонів у режимі імпульсного потенціалу. Запропоновано критерій застосовності отриманої формули, що дозволяє визначити критичні параметри режиму імпульсного потенціалу. Приведено розрахунки напруги в алмазоподібних покриттях при осадженні низькоенергетичних іонів C+ з фільтрованої плазми вакуумної дуги. Констатується якісна згода розрахункової напруги з експериментальними даними. Відзначається важлива роль температури осадження при контролі внутрішньої напруги в осаджуваному покритті.